Determining causes of death among individuals with haemophilia in Afghanistan. Issue 1 (26th November 2021) - Mousavi, Seyed Hamid; Arif, Shamim; Madadi, Shekiba; Mansouritorghabeh, Hassan
Abstract: Introduction: Haemophilia is a well‐known bleeding disorder that affects people worldwide. The main therapeutic strategy is regular infusion of exogenous factor VIII to ensure an optimal haemostatic standard. Morbidity and mortality of individuals with haemophilia has decreased in developing countries due to improvement in early detection, advanced treatments, and comprehensive population outreach efforts. However, individuals with bleeding disorders in developing countries like Afghanistan do not have access to such therapeutic facilities. Aims: The goals of this study were to determine the causes of death and findings related to death among in individuals with bleeding disorders in Afghanistan. Methods: This study conducted as a retrospective cross‐sectional study of 387 individuals with bleeding disorders (mainly haemophilia) in Afghanistan. Results: All registered individuals with bleeding disorders in Afghanistan were interviewed by telephone. Among the 387 individuals with bleeding disorders, there were 136 deaths. Most deaths occurred in individuals aged 1–15 years (66.2%). Intracranial haemorrhage was the leading cause of death in individuals with haemophilia A and B. Conclusion: These findings revealed that supply of coagulation factor concentrates, facilities for haemostasis diagnosis, and trained haematologists is inadequate in Afghanistan.